The influence of deep water circulation on the distribution of 231Pa and 230Th in the Pacific Ocean - Luo, Yiming; Lippold, Jörg; Allen, Susan E.; Tjiputra, Jerry; Jaccard, Samuel L.; Francois, Roger (Earth and planetary science letters, 2021)
Sedimentary 231Pa/230Th ratios have been used in the Atlantic Ocean as a proxy to reconstruct past changes in the strength and geometry of the Atlantic Meridional Overturning Circulation (AMOC), stemming from the southward export of 231Pa by the North Atlantic Deep Water (NADW). However, deep waters in the Pacific Ocean have a longer residence time, so that Pacific sedimentary 231Pa/230Th ratios are more strongly affected by particle/boundary scavenging, which obscures the influence of deep water circulation. The goal of this study is to examine how the Pacific Meridional Overturning Circulation (PMOC) affects the distribution of 231Pa and 230Th in the water column and sediment of the Pacific Ocean, and to explore whether sedimentary 231Pa/230Th ratios could provide useful constraints on past changes of the deep Pacific circulation. We examine the existing Pacific sedimentary 231Pa/230Th database and demonstrate that the Pacific Meridional Overturning Circulation (PMOC) has a distinctive influence on the distribution of sedimentary 231Pa/230Th. Using a 2D scavenging model with a simplified representation of the Pacific deep water circulation, we show that Pacific sedimentary 231Pa/230Th could potentially provide information on past variability in PMOC.
Im Titel sind die Zahlen "231" und "230" hochgestellt
Available online 27 November 2020
Gesehen am 17.02.2021